Pengaruh Kegiatan Mozaik Terhadap Keterampilan Motorik Halus Anak Usia 5-6 Tahun Di TK GKPI Tarutung Kota - Dosnita Berutu; Winarti Agustina; Adiani Hulu (Lembaga Pengembangan Kinerja Dosen, 2023)
The aim of this research is to determine the effect of mosaic activities on the fine motor skills of children aged 5-6 years at the GKPI Tarutung City Kindergarten. The type of research used in the research is quantitative research with experimental research methods and the type of research design is one group pretest post-test design. The population in this study was all children aged 5-6 years at the GKPI Tarutung City Kindergarten, totaling 110 people, and the sampling technique, namely purposive sampling, was 25 children from class B2. Data collection techniques were carried out using observation sheets, interviews and documentation. Based on the recapitulation of data on children's fine motor skills before being given treatment (pretest) using mosaic activities, there were no BSB categories, 4% were in the BSH category, 80% were in the MB category, 16% were in the BB category. After being given treatment (post-test) using mosaic activities, there were 32% in the BSB category, 68% in the BSH category, none in the MB and BB categories. Furthermore, based on the results of the t test, the value of tcount ˃ ttable (49.729 ˃1.711) was obtained. So it can be concluded that Ho is rejected and Ha is accepted, which means that there is an influence of mosaic activities on the fine motor skills of children aged 5-6 years at the GKPI Tarutung City Kindergarten.